Factors Influencing Consumer Purchase Intention in Social Media - Jibrin, Yusufu Chima (Eastern Mediterranean University - Doğu Akdeniz Üniversitesi, 2021)
A number of factors influence consumer purchase intention especially in the digital environment. With the advent of social media marketing, brands make effort to attract attention of consumers. The primary goal of this research is to explore the factors that influence brand purchase intention (BPI) of consumers in the context of social media environment. The factors examined included social media communication i.e. user generated (UGSMC) and firm-created communication (FCSMC), brand image (BI) and electronic word of mouth (eWOM). Their respective influence on brand purchase intention was analyzed. Necessary data was gathered via a random sampling technique where surveys were distributed at populated areas like restaurants and malls within Turkish Republic of Northern Cyprus. The data collected were analyzed using the SPSS statistical software to evaluate the relationship between the observed variables. Findings in this study demonstrated that UGSMC and BI have a positive effect on BPI. However, FCSMC and eWOM exhibited a negative association with BPI. This research contributes to existing literature by further affirming the importance of social media communication and building positive brand image in stimulating favorable purchase intention from customers. It also demonstrates how factors like trust and information overload could hinder the positive influence of firm-created communication and electronic word of mouth on consumer purchase intention. iv Keywords: Firm-communication, User-generated communication, Electronic word of mouth, Brand image, Purchase intention, Social media communication.

ÖZ:Dijital ortamda birçok faktör tüketicinin satın alma niyeti üzerinde etkili olmaktadır. Sosyal medya pazarlamasının gelişimi ile markalar tüketicilerin ilgisini çekmek için çaba harcamaktadır. Bu çalışma sosyal medya ortamı bağlamında tüketicilerin marka satın alma niyetini etkileyen faktörleri incelemeyi amaçlamaktadır. İncelemeye konu olan faktörler sosyal medya iletişimi (kullanıcı ve firmalar tarafından yaratılan), marka imajı ve elektronik ağızdan ağıza iletişimi içermektedir. Araştırma için gerekli olan veriler anket yöntemiyle Kuzey Kıbrıs Cumhuriyetinde restoran ve alışveriş merkezleri gibi kalabalık yerlerde rastlantısal örnekleme tekniği ile elde edildi. Söz konusu veriler gözlemlenen değişkenleri değerlendirmek üzere SPSS istatistik yazılımı ile analiz edildi. Çalışmanın bulguları kullanıcı tarafından yapılan sosyal medya iletişimi ve marka imajının tüketicilerin satın alma niyeti üzerinde olumlu bir etkisi olduğunu göstermiştir. Bununla beraber, firma tarafından yapılan sosyal medya iletişiminin tüketicilerin satın alma niyeti üzerinde olumsuz bir etkiye sahip olduğunu ortaya koymuştur. Bu araştırma sosyal medya iletişiminin ve tüketicilerin olumlu satın alma niyetlerini teşvik etmede pozitif marka imajı geliştirmenin önemini daha iyi ortaya koymuştur. Ayrıca, tüketici güveni ve aşırı bilgi gibi faktörlerin firma tarafında yapılan sosyal medya iletişimi ve elektronik ağızdan ağıza iletişimin tüketicilerin satın alma niyetleri üzerindeki olumlu etkisini azalttığını göstermiştir. vi Anahtar Kelimeler: Firma-tarafından yaratılan sosyal medya iletişimi, kullanıcı-tarafından yapılan sosyal medya iletişimi, Marka imajı, Satın alma niyeti.
Master of Arts in Marketing Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2021. Supervisor: Prof. Dr. Mehmet Haluk Köksal.
Keywords: Marketing Management; Purchase intention-Social Media-Cyprus (Turkish Republic of Northern Cyprus, 1983-); Word-of-mouth advertising; Marketing; Customer Satisfaction; Customer relations; Social media-Marketing; Communication in marketing; Firm-communication; User-generated communication; Electronic word of mouth; Brand image; Purchase intention; Social media communication